Ultra-durable Janus fabric treated with femtosecond laser for personal anti-fouling and thermal management - Ang Li; Bowen Chen; Jing Wu; Jiahui Gao; Juan Zhang; Xiangqian Guan (Polymer Testing)
Janus fabrics with moisture and heat-management capabilities are capable of improving the physiological and psychological comfort of humans. However, the current manufacturing processes for Janus fabrics are complex, expensive, and environmentally unfriendly. Moreover, the poor durability of the produced fabrics prevents them from meeting the requirements of daily use and washing. In this study, Janus fabric was prepared by spraying hydrophobic SiO2 particles onto hydrophilic cotton fabrics, followed by femtosecond-laser scanning. The prepared Janus fabric exhibited an excellent unidirectional liquid transport capability and could unidirectionally transport sweat from a hydrophobic to hydrophilic surface. The superhydrophobic surface of the Janus fabric provided outstanding antifouling properties, effectively preventing the adhesion of dirt and bacteria. More importantly, the Janus fabric could withstand approximately 1000 abrasion cycles and 30 accelerated washing cycles, which was a significant indication that it would be capable of daily use. In addition, the Janus fabric provided a cooler feeling than a conventional cotton fabric (≈4.9 °C lower than when wearing cotton fabric), and had an excellent water evaporation rate and moisture permeability. This method provided new insights into the development of economical and environmentally friendly ultradurable Janus fabrics.